Ultrasound-guided ankle block. History revisited. Issue 1 (March 2019) - Alain, Delbos; Philippe, Marty; Clément, Chassery; Olivier, Rontes; Coppens, Steve
Abstract: Following forefoot surgery, compared to the traditional multimodal approach, regional anesthesia and analgesia provides high quality pain relief, decreases opioids consumption and leads to very high satisfaction scores. Traditional regional techniques relied either on wound infiltration, landmark technique ankle blocks or popliteal sciatic nerve block. Numerous anatomic variations of the different nerves might lead to failure following a blind technique. The current evolution towards ambulatory care will push surgical teams to favor techniques that simplify postoperative treatment and encourages immediate ambulation. The development of Ultrasound Guided Blocks has enabled us to perform very selective and precise nerve blocks. Ankle blocks provide excellent intraoperative anesthesia as well as long postoperative pain relief. Complications are rare using regional anesthesia for postoperative analgesia even after extensive foot surgery. Revival of ankle blocks is a perfect example of the high impact of new technological advances in improving ambulatory surgical care after foot surgery.